Indonesia's Involvement in the Afghanistan Peacebuilding Process - Farizan, Fabian Nur; Heryadi, Dudy (Global: Jurnal Politik Internasional, 2020)
This article aims to understand and analyse Indonesia's involvement in ensuring peace, especially in peacebuilding efforts in Afghanistan. Indonesia’s commitment to improve its peace efforts in Afghanistan was expressed by President Joko Widodo during his visit to Kabul in 2018. This research used Lederach’s pyramid model of peacebuilding as the primary analysis tool. Lederach’s pyramid model identifies three approaches to peacebuilding, along with the main actors in the population affected by the conflict—namely top leadership, middle range leadership, and grass-root leadership. The results of the study show that Indonesia's involvement in Afghanistan in peace efforts has been carried out at all levels. Indonesia's peacebuilding efforts at the top level are focused on achieving Intra-Afghan Talks. At the middle range level, Indonesia runs capacity building programs and uses a religious approach through ulama. Furthermore, at the grassroots level, Indonesia focuses on empowering Afghan women as peace agents. The presence of Indonesia in all three approaches to Peacebuilding shows a positive mark for the overall Afghan peace process.